The Efficacy of Psychoeducation on Psychological Trauma Victims of Violent Communal Attack and Internally Displaced Persons (IDP) in Bassa Local Government Area of Plateau State, Nigeria - Yakubu, Ismaila; Dashit, Samson Ishaya (NIU Journal of Social Sciences, 2026)
Nigerian communities have experienced a succession of relentless and unending invasions stemming from banditry, communal violence, abduction and other types of insurgencies, leaving citizens in pain, devastation and despair. Undoubtedly, the readily accessible interventions mostly consisted of material support, which does not seem to focus on the mental and emotional aspects of the trauma. It is on this premise that this study investigated the interplay of community trauma incidents, psychoeducation and coping resources, together with the variability in the severity of traumatic experiences during the period of residence in internally displaced persons camps. An experimentation-based strategy was employed, with a total of N = 120 internally displaced individuals between the ages of 18 and 70 (mean age ≈ 44.00, SD = 15.01). A baseline test was administered to measure the severity of trauma among the participants; those with high scores were then randomly assigned to the control or intervention group. The result of an independent t-test for the difference in psychological trauma between the control and experimental groups at post-test showed a significant difference in mean scores of psychological trauma between the treatment and control groups: t (88) = 4.70, p < .001 (p < .05), with mean scores of 66.80 (control) and 60.71 (intervention). This implies that psychoeducation reduced psychological trauma for the victims of violent communal attacks. Also, a mediation analysis using Hayes’ PROCESS indicated lower levels of psychological trauma, suggesting that psychoeducation independently predicts reductions in psychological trauma, regardless of participants’ ages. In sum, psychoeducation intervention is a coping skill for managing psychological distress in a crisis-based situation. Therefore, employing a holistic approach that includes psychoeducation to manage traumatic conditions in Nigeria will help victims heal and recover from traumatic experiences.